Penyuluhan Literasi Keuangan Syariah Pada UMKM Kuliner Rufata - Harmaini, Harmaini; Indriyarti, Eko Retno; Diatmono, Prastiyo (Universitas Bunda Mulia, 2024)
Indonesia's large population is one of the marketing attractions of the financial market including Islamic finance. According to the 2022 National Survey of Financial Literacy and Inclusion (SNLIK), survey data indicates a noticeable rise in sharia financial literacy between 2019 and 2022. Nevertheless, more enhancements can be achieved by implementing outreach programs, counseling services, or training initiatives for the community, including business stakeholders. Consequently, the implementation team commenced sharing operations with the community by conducting outreach programs to disseminate information and understanding about sharia financial literacy to business actors that are members of the Rufata MSMEs in Jakarta. The outreach method was employed to conduct this action on December 9, 2023. The session proceeded successfully and seamlessly, with the participants displaying enthusiasm and active engagement in the conversation. Specifically, the findings of this study demonstrate that the participants, acting as business entities, have incorporated sharia finance into their financial practices by allocating a portion of their earnings towards zakat, infaq, and alms. In addition, the members have also established the segregation of corporate finances from household finances. The participants have moreover formulated uncomplicated financial strategies and allocated business revenue for future investments. Furthermore, the participants have expressed that they have acquired business funding sources without engaging in usury, and have diligently maintained records of their business financial reports. This exercise aims to enhance participants' proficiency in implementing sharia finance in business, hence strengthening these features.